Blockchain and Smart Contracts: A Paradigm Shift in Financial Regulatory Frameworks - Nasir Hussain Wali Mohammed Sayed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the integration of blockchain technology and smart contracts within financial regulatory systems and their potential to transform traditional compliance frameworks. The distributed and immutable nature of blockchain presents unique opportunities for enhancing regulatory reporting, fraud detection, and compliance monitoring in financial institutions. Through analysis of implementation cases and theoretical frameworks, this article identifies key applications in automated reconciliation, real-time monitoring, and cross-border regulatory coordination. Despite promising benefits in transparency and automation, significant challenges persist in scalability, legacy system integration, and regulatory uncertainty. This article contributes to the growing body of literature on regulatory technology by providing a comprehensive examination of blockchain applications in financial oversight, offering insights for both regulatory bodies and financial institutions navigating this technological transition. The articles suggest that while blockchain implementation requires substantial infrastructure adaptation, its potential to create more efficient, transparent, and secure regulatory systems warrants continued exploration and development.